Liposomes coated with N-trimethyl chitosan to improve the absorption of harmine in vivo and in vitro - Chen WL (Dove Medical Press, 2016)
Wei-liang Chen,1,* Zhi-Qiang Yuan,1,* Yang Liu,1 Shu-di Yang,1 Chun-ge Zhang,1 Ji-zhao Li,1 Wen-jing Zhu,1 Fang Li,1 Xiao-feng Zhou,2,3 Yi-mei Lin,4 Xue-nong Zhang1 1Department of Pharmaceutics, College of Pharmaceutical Sciences, 2Department of Radiobiology, College of Radiological Medicine and Protection, Soochow University, Suzhou, 3Changshu Hospital of Traditional Chinese Medicine, Changshu, 4The Second Affiliated Hospital of Xinjiang Medical University, Urumqi, People’s Republic of China *These authors contributed equally to this work Abstract: In this study, harmine liposomes (HM-lip) were prepared through the thin-film hydration–pH-gradient method and then coated with N-trimethyl chitosan (TMC). Particle size, zeta potential, entrapment efficiency, and in vitro release of HM-lip and TMC-coated harmine liposomes (TMC-HM-lip) were also determined. Sprague Dawley rats were further used to investigate the pharmacokinetics in vivo. Retention behavior in mouse gastrointestinal tract (GIT) was studied through high-performance liquid chromatography and near-infrared imaging. Degradation was further evaluated through incubation with Caco-2 cell homogenates, and a Caco-2 monolayer cell model was used to investigate the uptake and transport of drugs. HM-lip and TMC-HM-lip with particle size of 150–170 nm, an entrapment efficiency of about 81%, and a zeta potential of negative and positive, respectively, were prepared. The release of HM from HM-lip and TMC-HM-lip was slower than that from HM solution and was sensitive to pH. TMC-HM-lip exhibited higher oral bioavailability and had prolonged retention time in GIT. HM-lip and TMC-HM-lip could also protect HM against degradation in Caco-2 cell homogenates. The uptake amount of TMC-HM-lip was higher than that of HM and HM-lip. TMC-HM-lip further demonstrated higher apparent permeability coefficient (Papp) from the apical to the basolateral side than HM and HM-lip because of its higher uptake and capability to open tight junctions in the cell monolayers. TMC-HM-lip can prolong the retention time in the GIT, protect HM against enzyme degradation, and improve transport across Caco-2 cell monolayers, thus enhancing the oral bioavailability of HM. Keywords: harmine, liposomes, TMC, bioavailability, Caco-2 cell